An open source reading system for print disabilities - Nazemi, Azadeh; Murray, Iain (Institute of Information System & Research Center, 2013)
According to World Intellectual Property Organization (WIPO) estimation only 5% of the world’s one million print titles that are published every year are accessible to the some 340 million around the world who are blind, vision impaired or who live with other print disabilities. Access to information and education is an established human right. Many with print disabilities struggle to achieve equality in this area due to the lack of accessible books and sources of information. This research describes an approach to design a comprehensive reading system for vision impaired people.